## Solving the Equation: 0.4(3x - 0.5) = 1.5x + 0.2(x + 1)

This article will guide you through the steps of solving the given equation.

### Step 1: Distribute

Begin by distributing the constants outside the parentheses:

**0.4(3x - 0.5) = 1.5x + 0.2(x + 1)****1.2x - 0.2 = 1.5x + 0.2x + 0.2**

### Step 2: Combine Like Terms

Combine the 'x' terms and the constant terms on each side of the equation:

**1.2x - 0.2 = 1.7x + 0.2**

### Step 3: Isolate the Variable

Subtract 1.2x from both sides to isolate the 'x' term on the right side:

**-0.2 = 0.5x + 0.2**

Subtract 0.2 from both sides:

**-0.4 = 0.5x**

### Step 4: Solve for 'x'

Divide both sides by 0.5 to solve for 'x':

**-0.4 / 0.5 = x****-0.8 = x**

Therefore, the solution to the equation **0.4(3x - 0.5) = 1.5x + 0.2(x + 1)** is **x = -0.8**.